Incidental Exposure to Non-Like-Minded News through Social Media: Opposing Voices in Echo-Chambers’ News Feeds - Masip, Pere (2020)
Debates about post-truth need to take into account how news re-disseminates in a hybrid media system in which social networks and audience participation play a central role. Hence, there is a certain risk of reducing citizens’ exposure to politically adverse news content, creating ‘echo chambers’ of political affinity. This article presents the results of research conducted in agreement with 18 leading Spanish online news media, based on a survey (N = 6625) of their registered users. The results highlight that high levels of selective exposure that are a characteristic of offline media consumption are being moderated in the online realm. Although most of the respondents get news online from like-minded media, the figures related to those who also get news from media with a different media ideology should not be underestimated. As news consumption is becoming more ‘social,’ our research points out that Spanish citizens who are more active on social media sites are more likely to be exposed to news content from different ideological positions than those who are less active users. There is a weak association between the use of a particular social network site and gaining access to like- and non-like-minded news.